Impulsive Multiorders Riemann-Liouville Fractional Differential Equations - Weera Yukunthorn; Sotiris K. Ntouyas; Jessada Tariboon (Discrete Dynamics in Nature and Society)
Impulsive multiorders fractional differential equations are studied. Existence and uniqueness results are obtained for first- and second-order impulsive initial value problems by using Banach’s fixed point theorem in an appropriate weighted space. Examples illustrating the main results are presented.